Pengaruh Ekstrak Daun Singkong (Manihot esculenta Crantz) Sebagai Pembersih Smear Layer Pasca Preparasi Gigi - Juliantary, Sella Romika, drg. Noor Hafida Widyastuti., Sp.KG, drg. Ni Wayan Nindhia Eitsa Swastikasari (2016)
The process of tooth preparation or instrumentation, will produce a product such dentin's debris called as smear layer. Smear layer's product will preclude adhesion between dentin and restoration materials that can facilitate eleasing of material fillings from the tooth cavity, also it can be a host of bacteria that caused sustainable infection. Alternative materials for smear layer's cleaning is cassava leaf (Manihot esculenta Crantz) extract that containing saponin. Previous research, saponin known able to dissolve organic and inorganic compounds because it has characteristic such as detergents. The study was aimed to know the influence of cassava leaf (Manihot esculenta Crantz) extract as a smear layer cleaner in the tooth that has been prepared. Samples that used were bovine teeth which have similar content like human teeth. Bovine teeth were divided into group A,B, and negative control group. Each tooth prepared at the center of labial surface with a diameter 5mm and thickness 2mm, then cut into beam with length 7mm and wide 4mm. Group A was irrigated with polyacrylic acid 10% for 20 seconds then irrigated again with the sterile distilled water. Group B using cassava leaf (Manihot esculenta Crantz) extracts who irrigated for 20 seconds then irrigated again with the sterile distilled water. The negative control group was irrigated just with sterile distilled water. After irrigated, all of samples were incubated for 2x24 hours and then do SEM image and calculate the number of smear layer presence at the base of the cavity. Conclusion of the study using oneway ANOVA statistical test showed that p=0,00 (p<0,05) who that means cassava leaf (Manihot esculenta Crantz) extract has an influence on the cleanliness of the smear layer on the surface of the cavity after the preparation.